Functionalized ZIF‐90 for Gene‐mediated Chemotherapy to Ameliorate Multidrug Resistance in Breast Cancer Therapy. Issue 2 (10th November 2021) - Gong, Senyi; Shang, Mengdi; Li, Dawei; Cai, Yanfei; Jin, Jian; Yang, Zhaoqi
Abstract: Breast cancer, the most common cancer, is a threat to women's health. A great challenge for breast cancer is the multidrug resistance (MDR) problem. P‐glycoprotein (P‐gp) is one of main reasons to induce MDR in the therapy of breast cancer. A novel nanosystem based on ZIF‐90 was developed for alleviating MDR and to improve the therapeutic efficacy. In this investigation, ZIF‐90 was used as a carrier to deliver two kinds of DNA molecular beacons (MBs) and Doxorubicin (Dox). The loop sequences of two kinds of MBs were designed to specifically hybridize with the mRNAs related to P‐gp (MDR1 gene and ETS1 gene, respectively), thereby directly inhibiting the expression of downstream proteins P‐gp. The results of confocal fluorescence imaging and qRT‐PCR analysis indicated that MB and Dox were delivered into cells and the mRNAs related to P‐gp were silenced. The MTT assay showed that the IC50 of nanosystem to the drug‐resistant breast cancer cells (34.78 μg/mL) was much lower than the IC50 of Dox to the same cells (152.7 μg/mL). These results distinctly confirmed that the problem of MDR has been ameliorated by our designed nanosystem. It is our hope that this investigation may provide a new treatment strategy for enhancing the therapeutic efficacy of chemotherapy for breast cancer. Abstract : A novel nanosystem based on ZIF‐90 was developed for alleviating the MDR problem .Two kinds of MB were designed to specifically hybridize with the mRNAs related to P‐gp (MDR1 gene and ETS1 gene respectively). The results distinctly confirmed that the problem of MDR has been ameliorated by the designed nanosystem.